On Markov Chains and Filtrations - Peter Spreij (Tinbergen Institute, 1997)
In this paper we rederive some well known results for continuous time Markov processes that live on a finite state space.Martingale techniques are used throughout the paper. Special attention is paid to the construction of a continuous timeMarkov process, when we start from a discrete time Markov chain. The Markov property here holds with respect tofiltrations that need not be minimal.
Keywords: 330; Wahrscheinlichkeitsrechnung; Theorie